2010
DOI: 10.2478/s11756-009-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Fluctuating Asymmetry of the biggest Caspian whipsnake population in Hungary compared to a common snake species

Abstract: Abstract:The Fluctuating Asymmetry (FA) is a special type of asymmetry in the populations of bilaterally symmetrical creatures. The FA gives us numerical data on the developmental instability of the populations and refers to potential genetical and environmental stressors affecting the populations. Here we give the first data on the FA of the protected Caspian whipsnake (Hierophis caspius) from Hungary. The FA indices of the biggest population from Villány Mts were compared to the FA indices of two differently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Reptiles have proven especially conducive to studies on the causes and consequences of morphological aberrations because their scalation can readily be quantified meristically 25 . Thus, numerous studies on reptiles have explored the causes of scalation asymmetries and abnormalities 10 , 28 31 , their frequencies in different environments 14 , 17 , 23 , 32 34 and their consequences 35 – 40 . Nonetheless, few studies have identified both the sources of a trait and their impacts on organismal performance 8 , 30 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles have proven especially conducive to studies on the causes and consequences of morphological aberrations because their scalation can readily be quantified meristically 25 . Thus, numerous studies on reptiles have explored the causes of scalation asymmetries and abnormalities 10 , 28 31 , their frequencies in different environments 14 , 17 , 23 , 32 34 and their consequences 35 – 40 . Nonetheless, few studies have identified both the sources of a trait and their impacts on organismal performance 8 , 30 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous studies (Bellaagh et al 2010;Dudás 2018, 2019), we analysed a larger number of individuals of D. caspius. Biometric and morphological information has confirmed previously-described differences between sexes (Fuhn and Vancea 1961;Kotenko et al 1986) with maximum length of males not exceeding the previously-described range, although seven females were longer than previously recorded (Fuhn and Vancea 1961).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal row was treated as in Brown et al (2017). All scales around the eye (subocular, preocular, supraocular and postocular) were treated as perioculars, as applied previously (Bellaagh et al 2010). The scales around the mouth (upper labials and lower labials) were treated as labials.…”
Section: Methodsmentioning
confidence: 99%
“…Given its relationships with genetics and environmental conditions, FA can therefore be used to evaluate a species or population's conservation status (Bellaagh et al . ; Kourmpetis & Aravanopoulos ). However, the review by Bjorksten et al .…”
Section: Introductionmentioning
confidence: 99%